2013
DOI: 10.1371/journal.pone.0082355
|View full text |Cite
|
Sign up to set email alerts
|

Development, Alteration and Real Time Dynamics of Conjunctiva-Associated Lymphoid Tissue

Abstract: PurposeConjunctiva-associated lymphoid tissue (CALT) is thought to play a key role in initiating ocular surface related immune responses. This study was planned to get first profound insights into the function of CALT related to development, cellular dynamics and morphological alteration using a novel mouse model.MethodsExpression and morphology of CALT were investigated using BALB/c mice kept under different housing conditions, after topical antigen-stimulation and following lymphadenectomy and splenectomy. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 35 publications
3
52
0
2
Order By: Relevance
“…Moreover adaptive immune cells like T and B lymphocytes are present in the conjunctiva either diffusely distributed through epithelial or stromal layers or in loosely organized follicular structures, together forming Conjunctiva Associated Lymphoid Tissue (CALT). The presence of such CALT has been reported in both rodents and humans [6-8]. While CALT is a normal and non-inflammatory component of the ocular surface in human conjunctiva, in mice CALT is detected in response to antigenic challenge.…”
Section: Conjunctival Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover adaptive immune cells like T and B lymphocytes are present in the conjunctiva either diffusely distributed through epithelial or stromal layers or in loosely organized follicular structures, together forming Conjunctiva Associated Lymphoid Tissue (CALT). The presence of such CALT has been reported in both rodents and humans [6-8]. While CALT is a normal and non-inflammatory component of the ocular surface in human conjunctiva, in mice CALT is detected in response to antigenic challenge.…”
Section: Conjunctival Immune Cellsmentioning
confidence: 99%
“…While CALT is a normal and non-inflammatory component of the ocular surface in human conjunctiva, in mice CALT is detected in response to antigenic challenge. Organized follicles of mouse CALT contain T and B lymphocytes and follicular dendritic cells (Figure 1) [6]. Similar to gastric and airway mucosa CD11b+ and CD103+ subsets of dendritic cells are detected in murine conjunctiva [9] and contribute significantly to local immune response.…”
Section: Conjunctival Immune Cellsmentioning
confidence: 99%
“…8 Evidence from histological studies have led to the hypothesis that CALT is an active immunological interface responsible for detection of ocular surface antigens and is involved in initiating and regulating local ocular surface-related immune responses. 2,3,6,[9][10][11] In humans and in numerous studies conducted on rabbits, dogs, mice, and guinea pigs, CALT presented morphologic and functional features analogous to MALT described in other regions. [10][11][12][13][14] Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783…”
mentioning
confidence: 92%
“…Furthermore, we here confirmed that the mRNA expression of Th2-associated chemokines, such as CCL17/ TARC and CCL22/MDC, is significantly increased in the conjunctiva of AKC mice, which suggested that marked conjunctival allergic inflammation was crucial to the development of iCALT. The presence of CALT in conjunctival tissues has so far been reported in humans [12] , chickens [13] , rabbits [14] , guinea pigs [15] and mice [16,26,27] , although there are differences in the anatomical features, such as the location and size, across species. Histological characteristics common in CALT are the presence of lymphoepithelium, including M cells [28] , dome and parafollicular areas, including CD4-positive T cells, and a follicular area formed by B cells.…”
Section: Discussionmentioning
confidence: 99%